Spontaneous release of lipopolysaccharide by Pseudomonas aeruginosa. - Cadieux, J E (1983)
Pseudomonas aeruginosa PAO grown in glucose mineral salts medium released lipopolysaccharide which was chemically and immunologically similar to the cellular lipopolysaccharide. In addition, it possessed identical phage E79-inactivating properties. Through neutralization of phage activity and hemolysis inhibition assays, the organism was found to liberate lipopolysaccharide at a constant rate during log-phase growth equivalent to 1.3 to 2.2 ng/10(8) cells over a growth temperature range of 25 to 42 degrees C. At 19 degrees C, a lipopolysaccharide was released which was deficient in phage-inactivating activity but retained its immunological properties. Chemical analysis of lipopolysaccharide extracted from cells grown at 19 degrees C showed a deficiency in the O-side-chain component fucosamine. Gel exclusion chromatography of the polysaccharide fraction derived from lipopolysaccharide isolated from cells grown at 19 degrees C exhibited a decreased content of side-chain polysaccharide as well as a difference in the hexosamine:hexose ratio. The results of sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis confirmed these results as well as establishing that an essentially normal distribution of side-chain repeating unit lengths were to be found in the 19 degrees C preparation. These results suggest a decrease in the frequency of capping R-form lipopolysaccharide at 19 degrees C.